A comparison of pesticide residues in soils from two highly technified agricultural valleys in northwestern Mexico. Issue 6 (30th June 2021) - García-Hernández, Jaqueline; Leyva-Morales, José Belisario; Bastidas-Bastidas, Pedro de Jesús; Leyva-García, Germán Nepomuceno; Valdez-Torres, José Benigno; Aguilar-Zarate, Gabriela; Betancourt-Lozano, Miguel
Abstract: A pesticide characterization is presented for two highly technified valleys in northwest Mexico: Culiacan Valley (CV) in Sinaloa and Yaqui Valley (YV) in Sonora. Approximately 250, 000 kg of active ingredients are used every year, half of which are considered highly hazardous pesticides. Legacy pesticides are still present in the soils of these valleys. The aim of the present study was to identify and quantify a wide variety of pesticides in soils and correlate their concentrations with historical and current use. Agricultural soils from both valleys were sampled and analyzed using accelerated solvent extraction and subsequent quantification by gas chromatography with selective detectors. The most frequently detected pesticides (mean, µg g −1 ) in CV were organochlorines (0.1967), organophosphates (0.0928), synthetic pyrethroids (0.2565), organonitrogen (0.0552), and miscellaneous pesticides (0.1851). In YV, the most frequently detected pesticides were organochlorines (0.8607), organophosphates (0.0001), synthetic pyrethroids (0.0124), and miscellaneous pesticides (0.0009). The pesticides were more diverse in CV compared to those of YV, which was based on the types of crops produced. Both locations presented highly hazardous pesticides, including concentrations above the action levels established by the Canadian Soil Quality Guide. A follow-up risk assessment is recommended to assess potential effects.